Business model innovation : strategic and organizational issues for established firms - Markides, Constantinos (Cambridge : Cambridge University Press, 2023)
This text approaches the topic of business model innovation from the perspective of the established firm and examines the unique strategic and organizational issues that big, established companies face when a new business model enters their markets.
Also issued in print: 2023.
Includes bibliographical references.
Specialized.
Description based on online resource; title from PDF title page (viewed on June 6, 2023).
Keywords: Business planning; Strategic planning